Theoretical description of optical properties in III-V semiconductor nanostructures - Meier, Torsten; Landmann, Marc; Pochwala, Michal; Foerstner, Jens; Rauls, Eva; Schmidt, Wolf Gero (DPG Spring meeting 2010)
We present a joint theoretical study of the optical properties of GaAs and AlAs bulk and heterostructures. Thereby, we compare the theoretical description of optical excitation on several levels of theory. Results obtained from kp theory are discussed along with data from ab initio calculations within the frameworks of independent-particle (DFT), independent quasiparticle (GW), or Coulomb-correlated quasiparticle (BSE) approximation.

Modeling excitonic line shapes in weakly disordered semiconductor nanostructures - Kuznetsova, I.; Gőgh, N.; Förstner, Jens; Meier, Torsten; Cundiff, S. T.; Varga, I.; Thomas, P. (Physical Review B)
Excitonic spectra of weakly disordered semiconductor heterostructures are simulated on the basis of a one-dimensional tight-binding model. The influence of the length scale of weak disorder in quantum wells on the redshift of the excitonic peak and its linewidth is studied. By calculating two-dimensional Fouriertransform spectra we are able to determine the contribution of disorder to inhomogeneous and also to homogeneous broadenings separately. This disorder-induced dephasing is related to a Fano-type coupling and leads to contributions to the homogeneous linewidth that depends on energy within the inhomogeneously broadened line. The model includes heavy- and light-hole excitons and yields smaller inhomogeneous broadening for the light-hole exciton if compared to the heavy-hole exciton, which agrees qualitatively with the experiment.
Keywords: tet_topic_qw

Anticrossing of Whispering Gallery Modes in microdisk resonators embedded in an anisotropic environment - Declair, S.; Meier, Cedrik; Meier, Torsten; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
We numerically investigate the behavior of Whispering Gallery Modes (WGMs) in circularly shaped resonators like microdisks, with diameters in the range of optical vacuum wavelengths. The microdisk is embedded in an uniaxial anisotropic dielectric environment. By changing the optical anisotropy, one obtains spectral tunability of the optical modes. The degree of tunability strongly depends on the radial (azimuthal) mode order M (N). As the modes approach each other spectrally, anticrossing is observed, leading to a rearrangement of the optical states.
Keywords: tet_topic_microdisk

Coherent control of a single exciton qubit by optoelectronic manipulation - Michaelis de Vasconcellos, S.; Gordon, S.; Bichler, M.; Meier, Torsten; Zrenner, Artur (Nature Photonics)
The coherent state manipulation of single quantum systems is a fundamental requirement for the implementation of quantum information processors. Exciton qubits are of particular interest for coherent optoelectronic applications, in particular due to their excellent coupling to photons. Until now, coherent manipulations of exciton qubits in semiconductor quantum dots have been performed predominantly by pulsed laser fields. Coherent control of the population of excitonic states with a single laser pulse, observed by Rabi oscillations, has been demonstrated by several groups using different techniques1,2,3. By using two laser pulses, more general state control can be achieved4, and coupling of two excitons has been reported5,6. Here, we present a conceptually new approach for implementing the coherent control of an exciton two-level system (qubit) by means of a time-dependent electric interaction. The new scheme makes use of an optical clock signal and a synchronous electric gate signal, which controls the coherent manipulation.

Self-assembled quantum dots in a liquid-crystal-tunable microdisk resonator - Piegdon, Karoline A.; Offer, Matthias; Lorke, Axel; Urbanski, Martin; Hoischen, Andreas; Kitzerow, Heinz-Siegfried; Declair, Stefan; Förstner, Jens; Meier, Torsten; Reuter, Dirk; Wieck, Andreas D.; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)
GaAs-based semiconductor microdisks with high quality whispering gallery modes (Q44000) have been fabricated.A layer of self-organized InAs quantumdots (QDs) served as a light source to feed the optical modes at room temperature. In order to achieve frequency tuning of the optical modes, the microdisk devices have been immersed in 4 – cyano – 4´-pentylbiphenyl (5CB), a liquid crystal(LC) with a nematic phase below the clearing temperature of TC≈34°C .We have studied the device performance in the temperature rangeof T=20-50°C, in order to investigate the influence of the nematic–isotropic phase transition on the optical modes. Moreover,we havea pplied an AC electric field to the device,which leads in the nematic phase to a reorientation of the anisotropic dielectric tensor of the liquid crystal.This electrical anisotropy can be used to achieve electrical tunability of the optical modes.Using the finite-difference time domain (FDTD) technique with an anisotropic material model, we are able to describe the influence of the liquid crystal qualitatively.
Keywords: tet_topic_qd; tet_topic_microdisk

Reversal of Coherently Controlled Ultrafast Photocurrents by Band Mixing in Undoped GaAs Quantum Wells - Priyadarshi, S.; Racu, A. M.; Pierz, K.; Siegner, U.; Bieler, M.; Duc, H. T.; Förstner, Jens; Meier, Torsten (Physical Review Letters)
It is demonstrated that valence-band mixing in GaAs quantum wells tremendously modifies electronic transport. A coherent control scheme in which ultrafast currents are optically injected into undoped GaAs quantum wells upon excitation with femtosecond laser pulses is employed. An oscillatory dependence of the injection current amplitude and direction on the excitation photon energy is observed. A microscopic theoretical analysis shows that this current reversal is caused by the coupling of the light- and heavy-hole bands and that the hole currents dominate the overall current response. These surprising consequences of band mixing illuminate fundamental physics as they are unique for experiments which are able to monitor electronic transport resulting from carriers with relatively large momenta.
Keywords: tet_topic_qw

Enhanced FDTD edge correction for nonlinear effects calculation - Classen, C; Förstner, Jens; Meier, Torsten; Schuhmann, R (2010 IEEE Antennas and Propagation Society International Symposium)
The electromagnetic field in the vicinity of sharp edges needs a special treatment in numeric calculation whenever accurate, fast converging results are necessary. One of the fundamental works concerning field singularities has been proposed in 1972 [1] and states that the electromagnetic energy density must be integrable over any finite domain, even if this domain contains singularities. It is shown, that the magnetic field H(, ϕ) and electric field E(, ϕ) are proportional to ∝ (t−1) for → 0. The variable is the distance to the edge and t has to fulfill the integrability condition and thus is restricted to 0 < t < 1. This result is often used to reduce the error corresponding to the singularity without increasing the numerical effort [2 - 5]. For this purpose, a correction factor K is estimated by inserting the proportionality into the wave equation. It is shown, that this method improves the accuracy of the result significantly, however the order of convergence is often not studied. In [4] a method to modify the material parameters in order to use analytic results to improve the numeric calculation is presented. In this contribution we will - inspired by the scheme given in [4] - develop a new method to estimate a correction factor for perfect conducting materials (PEC) and demonstrate the improvement of the results compared to the standard edge correction. Therefore analytic results (comparable to [1]) are consequently merged with the scheme in [4]. The main goal of this work is the calculation of the second harmonic generation (SHG) in the wave response of so-called metamaterials [6]. Frequently these structures contain sharp metallic edges with field singularities at the interfaces which have a strong impact on the SHG signals. Thus, an accurate simulation of singularities is highly important. However, the following approach can also be applied to many other setups, and one of them is shown in the example below.
Keywords: tet_topic_numerics

Tuning quantum-dot based photonic devices with liquid crystals - Piegdon, Karoline A.; Declair, Stefan; Förstner, Jens; Meier, Torsten; Matthias, Heiner; Urbanski, Martin; Kitzerow, Heinz-Siegfried; Reuter, Dirk; Wieck, Andreas D.; Lorke, Axel; Meier, Cedrik (Optics Express)
Microdisks made from GaAs with embedded InAs quantum dots are immersed in the liquid crystal 4-cyano-4’-pentylbiphenyl (5CB). The quantum dots serve as emitters feeding the optical modes of the photonic cavity. By changing temperature, the liquid crystal undergoes a phase transition from the isotropic to the nematic state, which can be used as an effective tuning mechanism of the photonic modes of the cavity. In the nematic state, the uniaxial electrical anisotropy of the liquid crystal molecules can be exploited for orienting the material in an electric field, thus externally controlling the birefringence of the material. Using this effect, an electric field induced tuning of the modes is achieved. Numerical simulations using the finite-differences time-domain (FDTD) technique employing an anisotropic dielectric medium allow to understand the alignment of the liquid crystal molecules on the surface of the microdisk resonator.
Keywords: tet_topic_qd; tet_topic_microdisk

Ultrafast Coherent Interactions in Quantum Wells Studied by Two-Dimensional Fourier Transform Spectroscopy - Meier, Torsten; Zhang, Tianhao; Kuznetsova, Irina; Yang, Lijun; Bristow, Alan D; Dai, Xingcan; Li, Xiaoqin; Thomas, P.; Mukamel, S.; Mirin, Richard P.; Cundiff, S.T. (Ultrafast Phenomena XVI: Proceedings of the 16th International Conference, Palazzo dei Congressi Stresa, Italy, June 9--13, 2008)

Generation and time‐resolved detection of coherently controlled electric currents at surfaces - Meier, Torsten; Güdde, Jens; Rohleder, M.; Koch, S.W.; Höfer, Ulrich (physica status solidi c)
We demonstrate a technique for the generation and detection of electron currents at surfaces on a femtosecond time scale with a contact-free experimental setup based on a combination of coherent control and photoemission spectroscopy. We have applied this technique for electrons excited into image-potential states on a Cu(100) surface that form a free-electron-like band in the direction parallel to the surface. The photogeneration of currents is described by optical Bloch equations for a multiband model. By incorporating field-induced interband and intersubband transitions together with intraband accelerations into the model, the observed phase dependence of the population and of the current can be reproduced.

Anticrossing of Whispering Gallery Modes in Microdisk Resonators Embedded in a Liquid Crystal - Förstner, Jens; Declair, S.; Meier, Cedrik; Meier, Torsten (Theoretical and Computational Nanophotonics Tacona-Photonics)
We numerically investigate Whispering Gallery Modes (WGM) in a subwavelength microdisk resonator [1] embedded in an uniaxial anisotropic liquid crystal environment. It is shown that the WGMs have anticrossing behavior when modes of different radial mode order M or azimuthal order N approach each other spectrally.
Keywords: tet_topic_microdisk

Coherent control in hybrid metal-semiconductor nanostructures - Meier, Torsten; Reichelt, Matthias (DPG Spring meeting 2009)
Recently it has been shown experimentally that it is possible to coherently control nano-optical excitations by using sophisticated shaped laser pulses. In this work a similar technique is used to theoretically investigate a hybrid nanostructure which consists of a metal aperture and a quantum wire. It is shown that one can concentrate the optically excited electron density at an arbitrary position due to wave packet dynamics by chosing particular frequency components and phases of the chirped laser pulse. The optimization process is performed with a genetic algorithm which is linked to a 3D-FDTD solver.

Shaping the spatiotemporal dynamics of the electron density in a hybrid metal-semiconductor nanostructure - Reichelt, Matthias; Meier, Torsten (Optics Letters)
A one-dimensional semiconductor nanostructure is locally excited through a metal aperture. It is shown that the electron density can be coherently localized at desired spatial and temporal positions by using nontrivially shaped laser pulses. To obtain the optimized laser field, Bloch equations for a tight-binding model system are solved together with a genetic pulse-shaping algorithm. Full three-dimensional finite-difference time-domain (FDTD) simulations of the Maxwell–Bloch equations confirm the predicted coherent spatiotemporal control.

Generation of injection currents in (110)-oriented GaAs quantum wells: experimental observation and development of a microscopic theory - Bieler, M.; Pierz, K.; Siegner, U.; Dawson, P.; Duc, H. T.; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XIII)
We have experimentally investigated injection currents generated by all-optical excitation of GaAs/AlGaAs quantum wells excited with 130 fs optical pulses. The currents have been detected via free-space THz experiments at room temperature. Our experiments prove that Coulomb effects strongly influence injection currents. This becomes most prominently visible when exciting light-hole exciton transitions. At this photon energy we observe a pronounced phase shift of the current transients which is due to oppositely oriented heavy-hole and light-hole type contributions. We are currently developing a microscopic theory based on a 14×14 k.p model in combination with the semiconductor Bloch equations to describe the observed features quantitatively. The combined theoretical and experimental approach will allow us to analyze the influence of the bandstructure and interaction effects on the injection current amplitude and current dynamics.
Keywords: tet_topic_qw

Microscopic theory of the linear and nonlinear Terahertz response of semiconductors - Meier, Torsten; Koch, S.W.; Kira, M.; Steiner, J.T.; Golde, D. (CLEO/Europe - EQEC 2009 - European Conference on Lasers and Electro-Optics and the European Quantum Electronics Conference)
The paper presents a theoretical analysis of the nonlinear THz response from the internal transitions of coherent and incoherent excitons based on the formulated microscopic THz theory. Moreover, the response of unexcited semiconductors to extremely intense THz fields is investigated .The intersubband transitions of optically excited quantum wells using linear THz spectroscopy is also studied. The computed differential transmission shows a characteristic Fano-like line shape of the intersubband resonance. The pure intersubband contribution is given by a simple Lorentzian. Applying the microscopic theory, the Fano features of the total response can be attributed to the phase-sensitive superposition of the intersubband transitions and the ponderomotive contribution. These results are in excellent agreement with recent experiments.

Ultrafast coherent photoelectron emission effects and their application for time-domain studies of current transport - Meier, Torsten; Koch, S.W.; Rohleder, M.; Gudde, J.; Hofer, U. (Conference on Lasers and Electro-Optics and 2009 Conference on Quantum electronics and Laser Science Conference)
By combining coherent control schemes and photoelectron spectroscopy it is possible to generate ultrafast current pulses at surfaces and in solids and to detect their decay directly in momentum space with femtosecond time resolution.

Determination of homogeneous and inhomogeneous broadenings of quantum-well excitons by 2DFTS: An experiment-theory comparison - Kuznetsova, Irina; Thomas, Peter; Meier, Torsten; Zhang, Tianhao; Cundiff, Steven T. (physica status solidi (c))
The recently developed two-dimensional Fourier-Transform-Spectroscopy (2DFTS) in the optical regime has been established as an elegant experiment, which has manifold of applications in the investigation of semiconductor nanostructures. Here we focus on the real and imaginary part 2DFT spectra. As predicted recently, using rephasing and non-rephasing modes, we are able to determine the homogeneous and inhomogeneous broadenings of coupled excitonic resonances even for weak disorder where photon-echo data are not useful. Computed real and imaginary parts of the 2DFTS for rephasing and non-rephasing modes are compared with experimental data of a GaAs quantum well. It is demonstrated, that phase sensitive data for the rephasing and non-rephasing modes are able to accurately provide the disorder induced broadening in a complex coupled system for each transition separately.

Microscopic analysis of high-harmonic generation in semiconductor nanostructures - Golde, Daniel; Meier, Torsten; Koch, Stephan W. (physica status solidi (c))
A microscopic analysis of the emitted radiation of a semiconductor nanostructure after excitation with an extremely intense ultrashort laser pulse is presented. It is shown that the extreme nonlinear optical response is not sufficiently described by pure interband transitions but one has to include intraband effects as well. Numerical solutions of extended Bloch equations that include the coupled inter- and intraband dynamics are presented. For large excitation intensities, the intraband effects strongly modify the polarization dynamics and lead to a strong enhancement of high-harmonic generation compared to pure interband dynamics.

Preface - Meier, Torsten; Michler, Peter (physica status solidi c)

Photo-and spin current generation and dynamics in semiconductor nanostructures - Meier, Torsten; Duc, Huynh Thanh; Foerstner, Jens (DPG Spring meeting 2009)
The band structure and wave functions of GaAs quantum wells are computed via k.p band structure theory including anisotropy and spin splitting. Using these results, the process of generating photocurrents by optical excitation is analyzed. Depending on the symmetry of the material, the direction of the laser beam, and the polarization direction of the light field/s, one can coherently generate charge and/or spin photocurrents on ultrashort time scales. The direction, the strength, and the dynamics of these photocurrents are computed and discussed.